PELATIHAN LAS LISTRIK DASAR UNTUK MASYARAKAT USIA PRODUKTIF LINGKUNGAN RW 10 DESA SIDANEGARA KECAMATAN CILACAP TENGAH KABUPATEN CILACAP - Ipung Kurniawan; pujono pujono pujono (Universitas Islam Indonesia, 2020)
Community service is an obligation which must be formed for lecturers in higher education. Training of electrical welding that had been conducted as a form of dedication to society aims to provide the understanding of the importance of skill in conducting the training of basic electrical welding. The objective of the community service was productive men surrounding RW 10 Sidanegara, Cilacap subdistrict. To choose the objective was based on some reason, i.e.,there were many productive men that could cause the effect of the number of unemployed increased. This actvity used two methods. The first method was giving te understanding of basic electrical welding theory. In this case, preaching and discussing method were conducted. The second method was practice in laboratory in order that they obtained skill of welding. The result of this activity was the increase of knowledge and skill about techniques of basic electrical welding. With the skill they obtained, it can give positive impacts for people in economy and social sector.